2014
DOI: 10.3109/10799893.2014.931431
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin in cancer chemoprevention and treatment: pharmacokinetics and molecular targets

Abstract: A variety of bioactive food components have been shown to modulate inflammatory responses and to attenuate carcinogenesis. Polyphenols isolated several years ago from various medicinal plants now seem to have a prominent role in the prevention and therapy of a variety of ailments. Mangiferin, a unique, important, and highly investigated polyphenol, has attracted much attention of late for its potential as a chemopreventive and chemotherapeutic agent against various types of cancer. Mangiferin has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 80 publications
0
39
0
7
Order By: Relevance
“…It also inhibited cell cycle progression via ATR-Chk1 DNA damage stress-response pathways, leading to cell cycle-arrest in leukemia cells at the G2/M phase [37]. Mangiferin targets several proinflammatory transcription factors, growth factors, cell-cycle proteins, cytokines, kinases, adhesion molecules, chemokines, and inflammatory enzymes by inhibiting the initiation, promotion, and metastasis stages of cancer [38]. Estrogen receptor alpha (ERα) and beta (ERβ) are two regulators of gene transcription responsible for breast cancer.…”
Section: Health Perspectivesmentioning
confidence: 99%
“…It also inhibited cell cycle progression via ATR-Chk1 DNA damage stress-response pathways, leading to cell cycle-arrest in leukemia cells at the G2/M phase [37]. Mangiferin targets several proinflammatory transcription factors, growth factors, cell-cycle proteins, cytokines, kinases, adhesion molecules, chemokines, and inflammatory enzymes by inhibiting the initiation, promotion, and metastasis stages of cancer [38]. Estrogen receptor alpha (ERα) and beta (ERβ) are two regulators of gene transcription responsible for breast cancer.…”
Section: Health Perspectivesmentioning
confidence: 99%
“…Mgf, serving as a potent polyphenol, has been shown to affect several biological processes, like inhibition of NF-kB and other transcription factors, reactive oxygen species (ROS), angiogenesis, and apoptosis including mitochondrial bioenergetics [29]. It is reported that the anticancer activity is achieved by cell cycle arrest and direct apoptosis, while its chemoprotective action could be attributed due to its antioxidant and anti-inflammatory activities [30]. These targets enable the chemopreventive actions of Mgf by inhibiting the initiation, promotion and metastasis of cancer.…”
Section: Targets For Antioxidant Properties Of Mgf: Molecular Levelmentioning
confidence: 99%
“…Based on the recent survey and review (Rajendran et al, 2015), we would confirm that this is the first study conducted to explore the anti-H. pyloric activity of MF on AGS cell line. The disk agar diffusion method was employed to investigate the anti-H. pyloric activity of MF (with different concentration) on H. pylori-infected AGS cells.…”
Section: Resultsmentioning
confidence: 80%
“…MFt a broad spectrum of pharmaceutical activities such as antioxidant, anti-inflammation, anti-microbial, anti-invasive, anti-tumor (Wauthoz et al, 2007;Singh et al, 2012;Anand et al, 2015). Enormous studies had indicated that MF might act as an anti-carcinogen in various cancer cell line model attributing to its antioxidant, anti-inflammatory, anti-proliferative (cytotoxic), anti-adhesive, and pro-apoptotic effect (Rajendran et al, 2015; du Plessis-Stoman et al, 2011). Moreover, the gastroprotective activity of mangiferin was reported in an animal model (Carvalho et al, 2007).…”
Section: Introductionmentioning
confidence: 99%